2002
DOI: 10.1029/2001jc001089
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency variations in global mean sea level: 1950–2000

Abstract: [1] Low-frequency variability in global mean sea level (GMSL) is studied for the period 1950 -2000 by interpolating sparse tide gauge data to a global grid using empirical orthogonal functions (EOFs) of sea level variability determined from TOPEX/Poseidon (T/P) altimeter data. Results are based on data with long-term trends removed. The fact that the results do not have secular trends is an artifact of the analysis and should not be interpreted as an indication that sea level is not rising. The EOF reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 29 publications
(46 reference statements)
5
91
1
Order By: Relevance
“…In particular, it has long been reported that nonseasonal GMSL anomalies are significantly correlated with El Niño-Southern Oscillation (ENSO), such that the GMSL is anomalously positive during warm El Niño phases and anomalously negative during cool La Niña phases (Nerem et al, 1999(Nerem et al, , 2010Chambers et al, 2002;Ngo-Duc et al, 2005;Landerer et al, 2008;Merrifield et al, 2009;Llovel et al, 2010Llovel et al, , 2011Boening et al, 2012;Cazenave et al, 2012Cazenave et al, , 2014Meyssignac and Cazenave, 2012;Stammer et al, 2013;Fasullo et al, 2013;Haddad et al, 2013;Meyssignac et al, 2013;Calafat et al, 2014;Dieng et al, 2014Dieng et al, , 2015Pugh and Woodworth, 2014). Recent papers argue that ENSO-related GMSL changes are essentially of barystatic origin, related to changes in the hydrological cycle, and patterns of precipitation and evaporation (Llovel et al, 2011;Boening et al, 2012;Cazenave et al, 2012Cazenave et al, , 2014Fasullo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has long been reported that nonseasonal GMSL anomalies are significantly correlated with El Niño-Southern Oscillation (ENSO), such that the GMSL is anomalously positive during warm El Niño phases and anomalously negative during cool La Niña phases (Nerem et al, 1999(Nerem et al, , 2010Chambers et al, 2002;Ngo-Duc et al, 2005;Landerer et al, 2008;Merrifield et al, 2009;Llovel et al, 2010Llovel et al, , 2011Boening et al, 2012;Cazenave et al, 2012Cazenave et al, , 2014Meyssignac and Cazenave, 2012;Stammer et al, 2013;Fasullo et al, 2013;Haddad et al, 2013;Meyssignac et al, 2013;Calafat et al, 2014;Dieng et al, 2014Dieng et al, , 2015Pugh and Woodworth, 2014). Recent papers argue that ENSO-related GMSL changes are essentially of barystatic origin, related to changes in the hydrological cycle, and patterns of precipitation and evaporation (Llovel et al, 2011;Boening et al, 2012;Cazenave et al, 2012Cazenave et al, , 2014Fasullo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For the Singapore area, the earlier rate was similar, but the later trend is somewhat higher, centered at 5 mm yr −1 . The larger regional trend since 1993 in the tropical Pacific and Indian Oceans has been attributed to considerable interannual and decadal sea level variability associated, respectively, with the ENSO and the North Pacific Decadal Oscillation (Trenberth and Hurrell, 1994;Chambers et al, 2002;Church et al, 2004Church et al, , 2006and Becker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The method is similar to that classically used to reconstruct past atmospheric or oceanic fields such as marine sea level pressure (Kaplan et al, 2000), sea surface temperature (Smith and Reynolds, 2003) and sea level (Chambers et al, 2002;Church et al, 2004;Llovel et al, 2009;Calafat and Gomis, 2009). The method developed in the present study combines spatial information on TWS from GRACE (over 2003-2008) with multi-decade-long (over 1980-2008) but sparse river level time series based on in situ gauges.…”
Section: Introductionmentioning
confidence: 99%